Filtering wireless (Wi-Fi) Internet access in public places. (March 2017) - Spacey, Rachel; Muir, Adrienne; Cooke, Louise; Creaser, Claire; Spezi, Valérie
This paper discusses selected results from the AHRC-funded 'Managing Access to the Internet in Public Librarie s ' (MAIPLE) project and explores Wi-Fi Internet access in UK public libraries. It investigates how this compares to commercial provision of public Wi-Fi. It discusses security issues, filtering of Wi-Fi access and acceptable use policies. A mixed methods approach was used involving a review of the literature, a questionnaire survey of UK public library authorities and five case studies of selected authorities. A majority of UK public library authorities offer Wi-Fi access to the public at one or more of their libraries and they generally have an authentication system in place for their users. The majority of survey respondents that provide Wi-Fi use filtering software. There are similarities and differences in the ways that public libraries and commercial outlets provide and manage access to their wireless networks. Differences mainly relate to security and privacy: these differences reflect to an extent the underlying purposes of providing public Wi-Fi access as well as legal obligations. In some ways, public library Wi-Fi access is better managed than commercially provided public services. Evidence from the case studies suggests reluctant acceptance of filtering on the part of public library authorities, based on a perceived need to balance providing access to information with providing a safe and trusted public space for all.